2021
DOI: 10.1038/s41598-021-89543-3
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature and esthesia in individuals with stroke

Abstract: Patients with sequelae of stroke commonly report somatosensory losses. It is believed that body temperature may be associated with tactile sensibility and sensorimotor recovery of these patients. Demonstrate the associations among tactile sensibility, cutaneous temperature, subjective temperature perception, and sensorimotor recovery of patients with stroke sequelae. 86 patients with stroke sequelae were included. Patients had standardized regions of interest (ROIs) assessed with infrared thermography (FLIR T6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Currently, in health sciences, there are several studies that analyze the role of DITI in different areas [ 13 , 14 , 15 ]. Likewise, in the neurological field, numerous studies have observed the validity of this technique in relation to muscular trophic processes, observing that there are structural and functional alterations in atrophied muscles that can be correlated to thermographic changes observed at the cutaneous level [ 16 , 17 ]. To show the correlation between the thermal characteristics of the body at the surface level and deep muscle activation in patients with neuromuscular disorders, thermographic tests have been associated with functional motor tests and other biomedical diagnostic images [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, in health sciences, there are several studies that analyze the role of DITI in different areas [ 13 , 14 , 15 ]. Likewise, in the neurological field, numerous studies have observed the validity of this technique in relation to muscular trophic processes, observing that there are structural and functional alterations in atrophied muscles that can be correlated to thermographic changes observed at the cutaneous level [ 16 , 17 ]. To show the correlation between the thermal characteristics of the body at the surface level and deep muscle activation in patients with neuromuscular disorders, thermographic tests have been associated with functional motor tests and other biomedical diagnostic images [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that thermography could be a valid tool in the assessment and monitoring of the level of muscle atrophy in relation to motor function. Since, in these types of patients, the decrease in metabolic and functional activity of the muscular system seems to be directly related to changes in the skin’s surface temperature, the analysis of the ΔT by DITI could be transcendental for understanding the physiology and functional response of trophic pathologies associated with permanent functional dependence [ 16 , 17 , 20 ]. If this were to be demonstrated in future studies, it would make it possible, on the one hand, to speed up patient evaluation processes and times compared to other diagnostic techniques, and on the other hand, to allow professionals to perform this evaluation without contact or ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…ODY temperature is an important homeostatic parameter that maintains physiological function [1]. Patients with sequelae of brain disease, such as stroke, cerebral palsy and brain injury, may experience somatosensory losses which resulting abnormal temperature in the plegic limb [2] and the regulation of body temperature contributes to the sensorimotor recovery of stroke patients [3]. Many studies have shown that the hypothalamus plays a critical role in thermoregulation [1,4] the anterior hypothalamus (POA) are two important nuclei involved in thermoregulation [5].…”
Section: Introductionmentioning
confidence: 99%